2004
DOI: 10.1074/jbc.m410244200
|View full text |Cite
|
Sign up to set email alerts
|

Human Rad54 Protein Stimulates DNA Strand Exchange Activity of hRad51 Protein in the Presence of Ca2+

Abstract: Rad51 and Rad54 proteins play a key role in homologous recombination in eukaryotes. Recently, we reported that Ca 2؉ is required in vitro for human Rad51 protein to form an active nucleoprotein filament that is important for the search of homologous DNA and for DNA strand exchange, two critical steps of homologous recombination. Here we find that Ca 2؉ is also required for hRad54 protein to effectively stimulate DNA strand exchange activity of hRad51 protein. This finding identifies Ca 2؉ as a universal cofact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 53 publications
6
86
0
Order By: Relevance
“…Human and yeast Rad54 were purified as described previously in ref. 19. Untagged hRad54 was produced by proteolytic cleavage of GST-hRad54 with thrombin, as previously described in ref.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human and yeast Rad54 were purified as described previously in ref. 19. Untagged hRad54 was produced by proteolytic cleavage of GST-hRad54 with thrombin, as previously described in ref.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro, Rad54 has several important activities, reflecting its multiple functions at different stages of HR (16). Rad54 stimulates DNA strand exchange (17-19) and DNA heteroduplex extension promoted by Rad51 (20), and it can translocate along double-stranded DNA (dsDNA) by using the energy of ATP hydrolysis (19,(21)(22)(23), displace Rad51 from dsDNA (24), and remodel chromatin (16). We recently showed that Rad54 is a HJ-processing enzyme that promotes branch migration of HJs (25) and D-loop dissociation (26).…”
mentioning
confidence: 99%
“…Previously, we showed that RAD54 has a similar effect on dsDNA binding by the RAD51 filament (47). Here, we wanted to test whether BLM may stimulate the DNA pairing activity of RAD51 by the same mechanism.…”
Section: Blmmentioning
confidence: 99%
“…Here, we wanted to test whether BLM may stimulate the DNA pairing activity of RAD51 by the same mechanism. As in our previous studies with RAD54 (47), we used a co-aggregation assay that measures formation of low speed sedimenting co-aggregates resulting from the homology-independent uptake of dsDNA by the RAD51-ssDNA filament (48). If BLM were to increase dsDNA binding affinity of the RAD51-ssDNA filament, we would expect to observe an increase in resistance of co-aggregates to solution ion strength.…”
Section: Blmmentioning
confidence: 99%
“…Fig. 1B shows a kymograph (a plot of spatial position vs. time) obtained for the real-time assembly of Rad51 (100 nM) on a single DNA molecule in the presence of ATP (1 mM) and calcium acetate (2 mM) to prevent ATP hydrolysis (30,31). At the beginning of the reaction, the DNA molecule is Ϸ14.0 m in length for the flow rate used.…”
Section: Real-time Visualization Of Rad51 Nucleoprotein Filament Assementioning
confidence: 99%